Seeking Spiritual Direction: The Motivation of the Contemporary Ghanaian Christian - George K. Kyeremeh; John Kwaku Opoku; Frances Emily Owusu-Ansah; Kwabena Agyeman-Badu (E-Journal of Religious and Theological Studies)
Traditionally, divination is believed to offer alternative solutions to the challenges of some Ghanaians, and its version in the Christian space is commonly known in Akan as Akwankyerɛ (spiritual direction). Given this, most contemporary Christians turn to Akwankyerɛ as the major hope in life to solve their daily problems. Consequently, spiritual centres and patronisers are fast growing and dominating Christianity in Ghana. Therefore, this study explores the reasons behind the Ghanaian contemporary Christians’ search for spiritual support. Forty participants, including spiritual practitioners and clients, were studied from a qualitative perspective. Interviews were conducted and recorded for analysis. The study showed that many participants do not only seek Akwankyerε to strengthen their religious affinity to a deity, but also for different reasons such as health, economic, psycho-social, and desire for justice. The study recommends the integration of trained counsellors into the practice of Akwankyerε. This study contributes to the discussion of the proliferation of Akwankyerε in Ghana.